2020
DOI: 10.5005/jp-journals-10024-2732
|View full text |Cite
|
Sign up to set email alerts
|

Validity of Cone-beam Computed Tomography in Assessment of Morphological Bony Changes of Temporomandibular Joints

Abstract: Aim:The aim of the current study was to correlate the clinical symptoms that are associated with temporomandibular disorder (TMD) to the osseous changes occurring in the affected temporomandibular joint (TMJ), as detected by cone-beam computed tomography (CBCT). Materials and methods: The clinical data of patients that presented with TMJ symptoms was collected and correlated with the CBCT findings for the same patients. Patient recruitment took place over a 1-year period in the Oral and Maxillofacial Surgery a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…A study reported that no significant correlation was found between degenerative changes verified in CBCT and clinical symptoms of TMD 29 . Another study evaluated whether a relationship existed between degenerative changes and bone quality of the mandibular condyle and articular eminence in patients with TMD, and no causality relationship between these factors was found 30 .…”
Section: Discussionmentioning
confidence: 97%
“…A study reported that no significant correlation was found between degenerative changes verified in CBCT and clinical symptoms of TMD 29 . Another study evaluated whether a relationship existed between degenerative changes and bone quality of the mandibular condyle and articular eminence in patients with TMD, and no causality relationship between these factors was found 30 .…”
Section: Discussionmentioning
confidence: 97%